Domed oblong brooches of Vendel Period Scandinavia - Rundkvist, Martin (Information not available, contact SND for more information, 2015)
The study's aim was to investigate oblong brooches of Vendel Period Scandinavia, i.e. Ørsnes types N & O and similar brooches, including transitional types surviving into the Early Viking Period. A database of 593 brooches from all of Scandinavia was studied and interpreted by typology, chronology, function, social significance, technological characteristics, production sites, interregional variation and ideological connotations. Unique brooches are described and discussed. Brooches from Uppåkra are also described and discussed, against the background of the new results. The study then puts forward two new seriation chronologies for Vendel Period female graves on Bornholm and in Sweden.

Purpose:

The aim of the study is to offer new perspectives on domed oblong brooches of Vendel period Scandinavia and transitional types which survived into the earliest Viking period. The new perspectives are based on a larger and more recent material base and a widened geographic scope, covering all of Scandinavia.

The dataset consists of a table with information on domed oblong brooches from Vendel period and early Viking period Scandinavia. The data includes inventory numbers, provenance, measurements, type and context. The data is downloadable in -xls and .csv format. The download package also contains the study article and a codebook.

Studien berör välvda ovala spännbucklor i vendeltidens Skandinavien, d.v.s. Ørsnes typer N & O och liknande spännbucklor, inklusive övergångstyper som levde kvar in i den tidiga vikingatiden. En databas på 593 föremål från hela Skandinavien används i studien. Föremålen studeras och tolkas med avseende på typologi, kronologi, funktion, social betydelse, tekniska egenskaper, produktionsplatser, interregional variation och ideologiska konnotationer. Avvikande spännbucklor samt sådana från Uppåkra beskrivs och diskuteras separat. Studien lägger även fram två nya relativa kronologier för vendeltida kvinnogravar på Bornholm och i Sverige.

Syfte:

Studiens syfte är att erbjuda nya perspektiv på välvda ovala spännbucklor i vendeltidens Skandinavien, och övergångstyper som levde kvar in i den tidiga vikingatiden. De nya perspektiven baseras på ett stort nytt dataunderlag samt har en bredare geografisk omfattning som täcker hela Norden.

Datasetet består av en tabell med information om välvda ovala spännbucklor från vendeltiden och vikingatiden. Uppgifterna innefattar bland annat inventarienummer, geografiskt läge, mätdata, typ och kontext. Data går att ladda ned i XLS- och CSV-format. Nedladdningspaketet innehåller också studieartikeln och en kodbok.
Domed oblong brooches of Vendel Period Scandinavia
Keywords: Vendel Era; vendeltid; Viking Age; vikingatid; finds; fynd; archaeology and history; arkeologi och historia; HISTORY; HISTORIA; Archaeology; Arkeologi